(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the context of the rapid growth in the production of polymeric materials used in almost all areas of human life, the process of generating names in this field of knowledge is also taking place, since any language reflects the era, therefore, the consolidation of terminology is often associated with an intensive growth of new knowledge in this area. The study of the features of the terminological system of the scientific and technical branch "Polymer " (on the example of modern English) as a specialized subsystem of the national language is correlated with the study of its vocabulary, most of which are terms.